Gynecology: Contribution of the Peruvian Society of Obstetrics and Gynecology in 70 years of institutional life - Cabrera Ramos, Santiago (2017)
The Peruvian Society of Obstetrics and Gynecology (SPOG) has had a relevant role in the development of Gynecology in Peru and has contributed in the unification of services of Obstetrics and Gynecology in our public hospitals that used to be separated. The SPOG has facilitated updating the science of Gynecology in our associates trhough its Journal, meetings, courses, symposia and round tables in the specialty in order to give our patients the best care, with efficacy and warmth.